Technical and physical performance over an English championship league season - Morgans, R.; Adams, D.; Mullen, R.; McLellan, C.; Williams, M. (International Journal of Sports Science and Coaching, 2014)
The English Championship League (ECL) has a demanding ten-month schedule possibly exposing players to residual fatigue if they play the majority of matches. When present, residual fatigue may be evidenced by reduced physical and technical match performances as the season advances. The aim of this study was to investigate if differences in physical and technical performance occurred across a season for 11 ECL footballers who played the majority of matches that season. From the home matches analysed, only total distance covered was different (p = 0.0258), where it peaked at mid-season compared to two months later (p = 0.0104). Team possession remained stable throughout the season. Relative total distance covered by the team when in possession was 72 m/min less (p < 0.0001) than out of possession. In summary, maintaining possession during matches may reduce physical demands imposed on players and help preserve performance throughout the season.